Similarities in Hypertension Status but Differences in Mortality Risk: A Comparison of 2017 ACC/AHA and 2018 Chinese Hypertension Guidelines - Chen, Kangyu; Su, Hao; Wang, Qi; Wu, Zhenqiang; Shi, Rui; Yu, Fei; Yan, Ji; Yuan, Xiaodan; Qin, Rui; Zhou, Ziai; Hou, Zeyi; Li, Chao; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Few studies investigated the concordance in hypertension status and antihypertensive treatment recommendations between 2018 Chinese Hypertension League (CHL) guideline and 2017 American College of Cardiology (ACC)/American Heart Association (AHA) guideline, and assessed the change of premature mortality risk with hypertension defined by ACC/AHA guideline. Methods We used the baseline data of China Health and Retirement Longitudinal Study (CHARLS) to estimate the population impact on hypertension management between CHL and ACC/AHA guideline. Mortality risk from hypertension was estimated using the data from China Health and Nutrition Survey (CHNS). Cox proportional hazards model was used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs). Results: Among 13,704 participants analyzed from the nationally representative data of CHARLS, 42.64% (95% confidence interval: 40.35, 44.96) of Chinese adults were diagnosed by both CHL and ACC/AHA guideline. 41.25% (39.17, 43.36) did not have hypertension according to either guideline. Overall, the concordance in hypertension status was 83.89% (81.69, 85.57). A high percentage of agreement was also found for recommendation to initiate treatment among untreated subjects (87.62% [86.67, 88.51]), and blood pressure (BP) above the goal among treated subjects (71.68% [68.16, 74.95]). Among 23,063 adults from CHNS, subjects with hypertension by CHL had a higher risk of premature mortality (1.75[1.50,2.04]) compared with those without hypertension. The association diminished for hypertension by ACC/AHA (1.46[1.07,1.30]). Moreover, the excess risk was not significant for the newly defined grade 1 hypertension by ACC/AHA (1.15[0.95,1.38]) when compared with BP<120/80mmHg. This contrasted with the estimate from CHL (1.54[1.25,1.89]). A same pattern was observed for total mortality. Conclusions: If ACC/AHA guideline was adopted, a high degree of concordance in hypertension status and initiation of antihypertensive treatment was found with CHL guideline. However, the mortality risk with hypertension was reduced with a nonsignificant risk for grade 1 hypertension defined by ACC/AHA.